The Effect of Augmented Reality-Based Proprioceptive Training Program on Balance, Positioning Sensation and Flexibility in Healthy Young Adults: A Randomized Controlled Trial - Lee, Jaewon; Yu, Jaeho; Hong, Jiheon; Lee, Dongyeop; Kim, Jinseop; Kim, Seonggil (Healthcare (Basel), 2022)
This study investigates whether Augmented Reality (AR)-based interventions can be as effective as physical therapists (PT) regarding balance, positioning sensation, and flexibility. A sample of 39 regular people who voluntarily participated in this study were randomly distributed into two groups. Then AR was applied in the experimental group and PT was applied in the control group. Variables were measured by Tetrax (static balance), Y-balance test (dynamic balance), CSMI (proprioception), and sit and reach test (flexibility). All measurements were analyzed using paired t-test and independent t-test. The exercise program of this study improved the stability index (ST) of the static balance in both groups after the intervention, and there was a significant difference (p < 0.05) at normal eye close (NC) and Pillow with eye close (PC) positions. Moreover, regarding the case of dynamic balance, there were significant differences in AR and PT groups to reach in all directions (p < 0.05). In the case of positioning sensation, there was no significant difference in both groups (p > 0.05), and there was a significant difference in flexibility (p < 0.05). When comparing the two groups, there was no significant difference in all categories (p > 0.05). As a result, AR can be considered an effective form of therapy and can be selected according to individual conditions.